Peran Dukungan Keluarga dan Stres Kerja terhadap Work – life balance pada Paramedis Keperawatan Wanita di Rumah Sakit Kota Medan - Putri Fatimah; Sjahril Effendy; Rahmi Lubis (Mahesa Research Center, 2022)
The research aims to examine the role of family support and job stress to work – life balance among women nursing paramedic at Medan city hospital. This research used quantitative method. Total 324 women nursing paramedic at Medan city hospital participated in this research. The measurement conducted by using family support scale, job stress scale and work – life balance scale. Data on this research was analyzed using regression test. The results of this research show that there was the role of family support and job stress to work – life balance among women nursing paramedic at Medan city hospital cause statistic shows that F value 90.602 > F table 19.493 and p = 0,000 < 0,050. Another result this research approve that there was the role of family support to work – life balance among women nursing paramedic at Medan city hospital cause statistic shows that T value 10.910 > T table 1.967 and p = 0,000 < 0,050. and result this research approve that there was the role of job stress to work – life balance among women nursing paramedic at Medan city hospital cause statistic shows that T value -8.260 > T table 1.967 and p = 0,000 < 0,050. Another result is perceived family support of women nursing paramedic at Medan city hospital categorized as high, experienced job stress women nursing paramedic at Medan city hospital categorized as high and work – life balance of women nursing paramedic at Medan city hospital categorized as low. Therefore, it is recommended that further research be carried out with qualitative methods or mixed design and consider other variables